Evaluation of the Performance Achievements of the Kepulauan Riau Province Regional Personnel Agency (BKAD) in 2025 - Nova Fajaryanto; Zikrianul Fitrah (Center for Maritime Policy Governance Studies (CMPGS), 2026)
Regional financial and asset accountability is a crucial element in strengthening transparent, compliant, and performance-oriented public governance, particularly for provincial governments responsible for managing budget execution, financial reporting, and regional asset administration. This study aims to evaluate the optimization of financial and asset accountability through the 2025 performance achievements of the Regional Financial and Asset Agency (BKAD) of Kepulauan Riau Province. The research employed a qualitative descriptive approach using secondary data as the sole source of analysis. Data were obtained from performance achievement reports, budget realization data, financial reports, asset management documents, regulatory references, and audit-related information. The data were analyzed through descriptive analysis, content analysis, and comparative performance assessment by comparing targets and realization values across key accountability indicators. The findings show that BKAD Kepulauan Riau Province achieved strong performance in 2025. The timeliness of APBD establishment reached 100%, APBD expenditure realization reached 94.55% against a target of 91% with an achievement level of 103.99%, and the timeliness of financial report submission reached 100%. In asset accountability, the Asset Management Index reached 2.70 against a target of 2.10, producing an achievement level of 128.6%, while IKU achievement also reached 100%. These results indicate that BKAD has demonstrated effective financial discipline, improved asset governance, and consistent institutional performance. The study concludes that optimizing financial and asset accountability requires continuous integration of regulatory compliance, internal control, audit follow-up, data reliability, and performance-based transparency to support accountable regional governance.